(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
In recent decades, the frequency of natural and anthropogenic accidents has increased worldwide. The large unplanned expansion of cities to accommodate rapid population growth, combined with unplanned field use and the failure of city governments to regulate building standards, contributes to the vulnerability of urban populations. The author attempts to point out the need to apply a comprehensive model of Protection and Rescue because current models and concepts are limited to the tasks that they theoretically conceptually include as well as the time phases in which they operate in the event of an accident. The solution is in the comprehensive Civil Defence Emergency Management Model, whose assessment of numerous accident risks relates to the process of identifying the occurrence, probability, and assumption of potential likelihood of different types of accidents within a general spatial and temporal framework of cities.